Pilot clinical trial of neoadjuvant toll-like receptor 7 agonist (Imiquimod) immunotherapy in early-stage oral squamous cell carcinoma - Yoon, Angela J.; Carvajal, Richard D.; Graboyes, Evan M.; Kaczmar, John M.; Albergotti, William G.; Kejner, Alexandra E.; Troob, Scott H.; Philipone, Elizabeth; Anoma, Jean-Sebastien; Armeson, Kent E.; Hill, Elizabeth G.; Richardson, Mary S.; et al. (Frontiers in Immunology, 2025)
BackgroundThere is no neoadjuvant immunotherapy for early-stage oral cancer patients. We report a single-arm, open-label, pilot clinical trial assessing the efficacy and safety of topical toll-like receptor-7 (TLR-7) agonist, imiquimod, utilized in a neoadjuvant setting in early-stage oral squamous cell carcinoma (OSCC).MethodsThe primary endpoint is reduction in tumor cell counts assessed by quantitative multiplex immunofluorescence and the immune-related pathologic response. The secondary endpoint is safety.Results60% of patients experienced a 50% reduction or greater in tumor cell count post-treatment (95% CI = 32% to 84%). Similarly, 60% of patients had immune-related major pathologic response (irMPR) with two complete pathologic responses, and 40% had partial response (PR) with the percent residual viable tumor ranging from 25% to 65%. An increase in functional helper and cytotoxic T-cells significantly contributed to a reduction in tumor (R=0.54 and 0.55, respectively). The treatment was well tolerated with the application site mucositis being the most common adverse event (grades 1-3), and no grade 4 life-threatening event. The median follow-up time was 17 months (95% CI = 16 months - not reached), and one-year recurrence-free survival was 93% of evaluable patients.ConclusionNeoadjuvant imiquimod immunotherapy could be safe and promising regimen for early-stage oral cancer.Trial registrationClinicalTrials.gov, Identifier NCT04883645.